Efficacy and Immunological Impact of Intrathecal Baclofen Pumps in Managing Spasticity in Multiple Sclerosis in Adult Patients: A Systematic Review - Billy McBenedict; Wilhelmina Hauwanga; Anna Pogodina; Jeshua Nathaniel Devan; Kang Suen Goh; Ryan Chun Chien Yau; Berley Alphonse; Lorena Adolphsson; Bruno Lima Pessôa (Sclerosis)
Background/Objectives: Multiple sclerosis (MS) is a chronic autoimmune disease marked by inflammatory demyelination in the central nervous system, leading to debilitating spasticity. Managing spasticity in MS remains a challenge, and intrathecal baclofen (ITB) therapy has emerged as a potential targeted treatment. This systematic review investigated the efficacy of ITB pumps in managing MS-related spasticity and explored their immunomodulatory effects. Methods: This review adhered to PRISMA guidelines and was submitted for registration retrospectively with the Open Science Foundation. A comprehensive literature search was conducted in PubMed, Embase, Scopus, and Web of Science from January 2013 to August 2024. Studies were included if they examined adult MS patients receiving ITB for spasticity, reporting outcomes related to spasticity and quality of life. Risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Tools, and findings were synthesized narratively. Results: Eight studies (n = 723 participants) met inclusion criteria. ITB was associated with significant reductions in spasticity severity and improvements in quality of life, with reduced reliance on oral antispasticity medications. Immunologically, ITB has demonstrated potential in modulating inflammatory pathways, downregulating pro-inflammatory cytokines, and shifting immune responses toward an anti-inflammatory profile. Common complications included catheter-related issues and infections, with low overall complication rates. Sensitivity analyses indicated robustness in outcomes across higher-quality studies. Conclusions: ITB pumps are effective in controlling spasticity and offer additional immunological benefits for MS patients. Further research should explore ITB’s long-term immunomodulatory effects and its potential in combined therapeutic strategies. The review was not financially supported, and no conflicts of interest were declared by the authors.